Transvaginal ultrasound for diagnosis of deep endometriosis involving uterosacral ligaments, torus uterinus and posterior vaginal fornix: prospective study. (9th November 2021) - Ros, C.; de Guirior, C.; Mension, E.; Rius, M.; Valdés‐Bango, M.; Tortajada, M.; Matas, I.; Martínez‐Zamora, M. Á.; Gracia, M.; Carmona, F.
ABSTRACT: Objective: To evaluate the accuracy of transvaginal ultrasound (TVS) in diagnosing deep endometriosis (DE) involving the uterosacral ligaments (USLs), torus uterinus (TU) or posterior vaginal fornix (PVF) in women with suspected endometriosis scheduled for laparoscopic surgery. Methods: In this prospective study, consecutive women with clinically suspected pelvic endometriosis who were scheduled for laparoscopic surgery were invited to participate. TVS was performed before surgery. TVS findings were compared with those obtained at laparoscopy and confirmed histologically. The accuracy of TVS for diagnosing DE involving the USLs, TU or PVF was assessed. Additionally, the association of DE involving the USLs, TU or PVF on TVS with symptoms and with DE affecting other pelvic locations was assessed. Results: In total, 172 patients were included. The global sensitivity and specificity of TVS in diagnosing DE affecting the USLs, TU and/or PVF were 92% and 87%, respectively. For DE involving the USLs, the accuracy, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio and negative likelihood ratio of TVS were 89.5%, 96.6%, 82.1%, 85.0%, 95.8%, 5.41 and 0.04, respectively; the respective values for DE involving the TU were 86.6%, 83.9%, 89.4%, 89.0%, 84.4%, 7.92 and 0.18, and the respective values for DE involving the PVF were 93.6%, 87.0%, 94.6%, 71.4%, 97.9%, 16.20 and 0.14. Logistic regression analysis showed a significant association between DE affecting the USLs, TU and/or PVF and DE affecting the rectosigmoid (odds ratio, 5.43; P < 0.001). Dyschezia was associated strongly with DE involving the USLs, TU and PVF, while dysmenorrhea was associated significantly with DE involving the TU. Conclusion: TVS has high accuracy, sensitivity, specificity, PPV and NPV for the detection of DE involving the USLs, TU and PVF in women with suspected endometriosis scheduled for laparoscopic surgery. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.